Students’ Perspectives on Religious Moderation in Pancasila Education: Insights into Multicultural Learning Practices - Ari Limay Trisno Putra; Ibnu Imam Al Ayyubi; Namiyah Fitriani; Alamul Huda Almuzakky (Sekolah Tinggi Ilmu Tarbiyah Bustanul Ulum Lampung Tengah, 2026)
The growing religious diversity and potential polarization in higher education highlight the urgency of strengthening religious moderation through civic education. However, limited studies have examined how students perceive and internalize religious moderation within Pancasila Education. This study analyzes students’ perspectives on the implementation of religious moderation in Pancasila Education in higher education. Grounded in the conceptual framework of religious moderation as a balanced, anti-extremist, and tolerance-based approach, this research employs a descriptive qualitative design. Data were collected through semi-structured interviews with students who had completed the Pancasila course and analyzed using an interactive qualitative analysis model. The findings reveal that students conceptualize religious moderation as a middle-path attitude that promotes harmony, justice, and respect for diversity. Pancasila learning particularly through dialogical discussions, contextual case studies, and reflective assignments facilitates the internalization of moderation values. The historical formulation of the first principle of Pancasila serves as a key entry point for understanding compromise and consensus in a plural society. However, challenges remain in translating conceptual understanding into consistent social practice. This study contributes by highlighting students’ perspectives as a micro-level lens to understand the internalization of religious moderation, reinforcing the role of Pancasila Education in fostering inclusive and moderate student character.